Optimización de la producción de los pozos productores de un campo en la Cuenca Llanos Orientales, mediante la implementación de análisis nodal (2020)
The nodal analysis implementation in a field in the Llanos Orientales basin allows the optimization of production, by means of the hydraulic simulation from the well to the arrival of the station where the treatment is carried out and the fluid is collected from 23 active wells. The nodal analysis shows that there are hydraulic restrictions and pressure losses along the pipes, which allowed optimization scenarios to be proposed to increase or optimize production. By using the specialized simulation software PIPESIM 2019.1 **, the wells and the surface network to the treatment station are created and modeled, taking into account the technical and operational aspects provided by Ecopetrol, so that the model represents current conditions of the field. Additionally, two optimization scenarios are created for the eight wells that present opportunities for improvement in crude oil production, seeking the operation of wells with low% BSW, as well as wells with partially closed choke valves, or that allow the increase of the pump frequency and as a last option consider scenarios that present changes in the pump stages.